Religiosity, accounting expertise, and audit report lag: Empirical evidence from the individual level - Abood Al-Ebel (Taylor & Francis Group, 2020)
Motivated mainly by three streams of research on religiosity and accounting expertise, this study investigates the effect of religiosity and accounting expertise on audit report lag. Using a unique sample and pooled regressions, it finds that the religiosity of top leaders, for example, Chief Executive Officer (CEO) and audit committee (AC) chair, is not associated with shorter audit report lag. Consistent with prior research, it reports that the accounting expertise of top leaders is significantly associated with shorter audit report lag. More importantly, it documents that a religious top leader with accounting expertise is significantly associated with a greater reduction in audit report lag. Robustness checks are applied by conducting a variety of tests, resulting in similar findings. In additional analysis, this paper documents that religious and accounting expertise of top leaders are associated with abnormal decrease in audit report lag and that Big4 audit firms interact with the religiosity and accounting expertise of the AC chair more than the CEO. Overall, this study sheds light on the added value of religiosity and accounting expertise in the context of audit report lag.